Development, characterization and in VIVO evaluation of diffusion controlled transdermal matrix patches of a model anti-Inflammatory drug - Kapoor, Bhawana; Bhatt, Sarswati Prakash; Bilandi, Ajay; Sahiba, Sahiba; Singh, Balraj; Kumar, Parveen (International journal of health sciences, 2022)
In the current research, diffusion controlled transdermal matrix patches of Lornoxicam, an anti-inflammatory drug was developed by solvent casting method using hydrophilic and hydrophobic polymers in different ratios and tween-80 and span-80 as permeation enhancers. Formulated patches were characterized for different physicochemical parameters in terms of moisture loss, drug content, film thickness and strength, uptake and loss of moisture, transmission of water vapor etc. All of these parameters were found be satisfactory. In-vitro diffusion studies of formulated patches were performed by using Franz diffusion cells. The drug diffusion rate followed zero order kinetics with super case II transport diffusion. Based on In-vitro diffusion data, best formulation was selected and used further for the stability analysis. Developed patches were stable at different temperature and humidity settings in terms of physicochemical properties and drug content. The optimized patches were also evaluated for the in-vivoanti-inflammatory and analgesic activity using suitable animal models. The results of all the in-vitro and in-vivo studies justify the selection of transdermal route for the systemic delivery of Lornoxicam to overcome its shortcomings when administered orally.